Reflexive Konstruktionen im Deutschen und Slowakischen im Vergleich - Alexandra Popovičová (Linguistische Treffen in Wrocław, 2021)
Both in German and in Slovak, the reflexive constructions, i.e. those with the component sich in German or sa/si (in the longer form seba/sebe) in Slovak, are common constructions with significant parallels but also contrasts in usage. The reflexivity is largely polysemantic in both languages; reflexivation can be motivated in different ways; the reflexive can have different morphosyntactic features and fulfil different functions. In the context of German-Slovak contrastive linguistics, the phenomenon of reflexivity has been dealt with rather peripherally. Therefore, the article aims to outline the similarities and contrasts of the reflexive constructions in both languages from the linguistic point of view, comparing their semantic and morphosyntactic features. It also aims to illustrate the most important functions of reflexivity. For this purpose, the approaches in German and Slovak grammar theories were analysed and compared using specific examples. The author discusses following categories: obligatory reflexive verbs, reflexive forms of non-reflexive verbs, verbs with semantic reflexivity, reciprocal verbs and reflexive constructions with passive perspective: reflexive passive, medio-passive and sich-lassen-constructions. The findings show that there is a terminological discrepancy between the two languages regarding the classes of verbs with reflexive pronoun, but this can be eliminated by an expanded definition. The reflexivity is polyfunctional in both languages. Rather than coreference, some of the most important functions of reflexivity are primarily expressing passive perspective and, especially in Slovak, the word formation. The most important difference derives from the fact that the reflexive passive in Slovak is considered to be the equivalent of the German werden-passive. In all respects it can be seen that the area of reflexivity in both languages extends far beyond verb semantics.